The Negative Impact of M&A Performance Betting Agreements on Investment Efficiency - Li, Shi (Transactions on Economics, Business and Management Research, 2024)
Analyzing A-share listed companies M&A samples from 2008 to 2022, the study finds that performance betting agreements negatively impact investment efficiency, with greater negative effects at higher commitment levels. The impact is more significant in unaffiliated and non-state-owned transactions, enriching the literature related to the economic consequences of performance guarantees and providing experience and insights for enterprises to improve M&A investment efficiency and for regulatory authorities to improve M&A restructuring systems.